The Effectiveness of Dance Therapy as an Adjunct to Rehabilitation of Adults With a Physical Disability - Swaine, Bonnie; Poncet, Frédérique; Lachance, Brigitte; Proulx-Goulet, Chloé; Bergeron, Vicky; Brousse, Élodie; Lamoureux, Julie; McKinley, Patricia (Frontiers in Psychology, 2020)
Background/Objective: To determine the added benefit on participants’ mobility and participation of a 12-week dance therapy (DT) intervention combined with usual physical rehabilitation for adults with varied physical disabilities. Their appreciation of DT was also explored. Methods: We conducted a quasi-experimental study pre-post test with a non-equivalent control group and repeated measurements pre, post and at 3-month follow-up. Results: Although participants in both groups significantly improved over time (at 12 weeks and at follow-up) compared to baseline on mobility (Timed up and go, TUG) and participation (e.g. Life-H scores and number of leisure activities), treatment effects analysis using propensity score matching showed no significant treatment effect of DT. The TUG scores showed the best promise of a treatment effect. DT participants’ Flow State Scale scores significantly improved (p <0.01) for 5/9 dimensions of flow (Being in control, Loss of self-consciousness) and they all recommended DT. Conclusions: This study failed to demonstrate an added benefit of the DT intervention in improving participants’ mobility and participation. Overwhelmingly favorable participants’ opinions about the intervention support its potential impact.